2011
DOI: 10.4155/fmc.11.158
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Inhibitors of Acats: Recent Advances and Promising Developments

Abstract: Acyl-CoA:cholesterol acyltransferase (ACAT) is a promising therapeutic target for cardiovascular diseases. Although a number of synthetic ACAT inhibitors have been developed, they have failed to show efficacy in clinical trials. Now, the presence of two ACAT isoforms with distinct functions, ACAT1 and ACAT2, has been discovered. Thus, the selectivity of ACAT inhibitors toward the two isoforms is important for their development as novel anti-atherosclerotic agents. The selectivity study indicated that fungal py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 157 publications
(184 reference statements)
0
29
0
Order By: Relevance
“…7 Unfortunately, there has been no report about the biological activity of terretonins A-D. 6 Accordingly, other biological activities of 1 in our in-house assays such as effect on cell cycle, 16 lipid metabolites 17 Terretonin G T Fukuda et al significant activity in these assays even at 25 mg ml À1 (data not shown). To our knowledge, this is the first report that terretonins showed antimicrobial activity.…”
mentioning
confidence: 78%
“…7 Unfortunately, there has been no report about the biological activity of terretonins A-D. 6 Accordingly, other biological activities of 1 in our in-house assays such as effect on cell cycle, 16 lipid metabolites 17 Terretonin G T Fukuda et al significant activity in these assays even at 25 mg ml À1 (data not shown). To our knowledge, this is the first report that terretonins showed antimicrobial activity.…”
mentioning
confidence: 78%
“…Accordingly, the graphiumins were evaluated in our in-house assays; antimicrobial assay, 35 mammalian cell cycle assay, 36 lipid metabolism assay 37 and bone morphogenetic protein-induced alkaline phosphatase expression assay. 38 However, they showed no activity in these assays even at 25 μg ml − 1 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…5) During the course of our screening program, microbial metabolites of beauveriolides, [6][7][8][9] phenochalasins, 10,11) spylidone, 12) sespendole, 13) isobisvertinol, 14) quinadoline B, 15) pentacecilide 16) and K97-0239 17) were found to be inhibitors of lipid droplet accumulation in macrophages, and some inhibitors were investigated in terms of inhibition of the mechanism of action of lipid droplet accumulation in macrophages. 18,19) From further screening studies, bufalin, a known cardiotonic steroid from Chinese toad 20) (Fig. 1), was found to possess such activity.…”
Section: -4)mentioning
confidence: 99%